Customized Slab-Segmentation Method for Projection-Artifact Elimination in Best Vitelliform Macular Dystrophy: A Swept-Source Optical Coherence Tomography Angiography Study - Moussa M (Dove Medical Press, 2021)
Magdy Moussa,1,2 Mahmoud Leila,3 Omar Moussa,2,4 Ahmed Osama Hashem4 1Ophthalmology Department, Faculty of Medicine, Tanta University, Tanta, Egypt; 2MEDIC Eye Center, Tanta, Egypt; 3Retina Department, Research Institute of Ophthalmology, Giza, Egypt; 4Ophthalmology Department, Faculty of Medicine, Kafr El Sheikh University, Kafr El Sheikh, EgyptCorrespondence: Magdy MoussaOphthalmology Department, Faculty of Medicine, Tanta University Campus, Tanta, 31111, EgyptTel +20-12 2316-1495Email magdymoussa60@gmail.comPurpose: To assess the efficacy of customized slab segmentation in eliminating projection artifacts in swept-source optical coherence tomography angiography (SS-OCTA) images of Best vitelliform macular dystrophy (BVMD).Methods: Prospective case series including different stages of BVMD. We analyzed SS-OCTA images for flow signals in the outer retina and coregistered B-scan images for distortion of the segmentation slabs defining the outer retina. We applied a customized method for slab realignment whenever BVMD lesions produced distortion of the slabs. Afterward, we checked the images to determine whether the previously noted flow signal had persisted or disappeared, described as “true flow” or “pseudoflow”, respectively. Categorical variables were analyzed with X2 or Fisher’s exact tests, while quantitative variables were analyzed with independent t-test at p< 0.05.Results: The study included 39 eyes of 22 patients. We detected BVMD patterns I (dome-shaped hyperreflective lesion without neurosensory retinal detachment), II (knob-like hyperreflective lesion with localized neurosensory retinal detachment), and III (heterogeneous scattered hyperreflective material) in 49%, 23%, and 28% of eyes, respectively. Pseudoflow was evident mostly in eyes with pattern II lesions, presence of flow signal within BVMD lesions, and lesions whose height represented > 80% of the retinal thickness (p< 0.001).Conclusion: Customized slab segmentation is effective in eliminating projection artifact in SS-OCTA images of BVMD.Summary: Projection artifact is a significant confounding factor in emerging SS-OCTA technology through production of pseudoflow signals that can lead to misinterpretation of images of BVMD lesions. The present study proposes a customized method for correction of segmentation errors to eliminate projection artifacts in SS-OCTA images of BVMD patients.Keywords: projection artifacts in SS-OCTA images, segmentation errors in BVMD images, SS-OCTA imaging of BVMD, customized slab segmentation in SS-OCTA images